Inhibitory Effect of Periodontitis through C/EBP and 11β-Hydroxysteroid Dehydrogenase Type 1 Regulation of Betulin Isolated from the Bark of Betula platyphylla - Eun-Nam Kim; Gil-Saeng Jeong (MDPI AG, 2022)
Periodontitis is an infectious inflammatory disease of the tissues around the tooth that destroys connective tissue and is characterized by loss of periodontal ligaments and alveolar bone. Currently, surgical methods for the treatment of periodontitis have limitations and new treatment strategies are needed. Therefore, this study evaluated the efficacy of the compound betulin isolated from bark of Betula platyphylla on the inhibition of periodontitis in vitro and in vivo periodontitis induction models. In the study, betulin inhibited pro-inflammatory mediators, such as tumor necrosis factor, interleukin-6, inducible nitric oxide synthase, and cyclooxygenase-2, in human periodontal ligament cells stimulated with Porphyromonas gingivalis lipopolysaccharide (PG-LPS). In addition, it showed an anti-inflammatory effect by down-regulating 11β-hydroxysteroid dehydrogenase type 1 and transcription factor C/EBP β produced by PG-LPS. Moreover, PG-LPS inhibited the osteogenic induction of human periodontal ligament cells. The protein and mRNA levels of osteogenic markers, such as inhibited osteopontin (OPN) and runt-related transcription factor 2 (RUNX2), were regulated by betulin. In addition, the efficacy of betulin was demonstrated in a typical in vivo model of periodontitis induced by PG-LPS, and the results showed through hematoxylin & eosin staining and micro-computed tomography that the administration of betulin alleviated alveolar bone loss and periodontal inflammation caused by PG-LPS. Therefore, this study proved the efficacy of the compound betulin isolated from B. platyphylla in the inhibition of periodontitis and alveolar bone loss, two important strategies for the treatment of periodontitis, suggesting the potential as a new treatment for periodontitis.